Zika, the Centers for Disease Control and Prevention, and Secrets Resorts: Using a viral outbreak to teach students about crisis communication. Issue 4 (1st October 2020) - McMonagle, Susannah K.
Abstract : Courses: Public Relations, Organizational/Crisis Communication, Social Media in Organizations. Objective: The goal for this activity is for students to simulate an organizational response to an environmental/health crisis impacting their business operations. By working through various components of a crisis event, students apply theoretical learnings and create messages for both internal and external stakeholders utilizing a variety of communication channels, including social media.